2020
DOI: 10.3126/njes.v8i1.34442
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater fish diversity and its conservation status in different water bodies of Nepal

Abstract: This review describes the current status of freshwater fish diversity, their IUCN categories and threats to fish fauna in Nepal. The freshwater systems of the country are known to harbor over 220 fish species, thereby indicating a rich ichthyofaunal diversity. However, this number varies from author to author. Cyprinidae is the most common and dominant taxon. A total of 15 endemic and 15 exotic fish species have been reported. A total of 34 fish species have been listed under the IUCN Red List threatened categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Considering more than 220 species reported from Nepalese freshwater ecosystems (Khatri et al 2020) and presence of 52 (about 23.6%) species in only ten sites indicate a rich fish faunal diversity from the Babai and the Bheri River systems. This is also evident from Pielou's evenness (Figure 3) which ranged from 0.3 (at site BBT1 during winter) to 0.9 (at site BH2 during winter) indicating rich diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering more than 220 species reported from Nepalese freshwater ecosystems (Khatri et al 2020) and presence of 52 (about 23.6%) species in only ten sites indicate a rich fish faunal diversity from the Babai and the Bheri River systems. This is also evident from Pielou's evenness (Figure 3) which ranged from 0.3 (at site BBT1 during winter) to 0.9 (at site BH2 during winter) indicating rich diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Nepal represents both Indo-Malayan and Palearctic realms (Chaturvedi 2012) and coupled with its rich network of rivers and streams (WECS 2011), the country harbours a rich terrestrial as well aquatic biodiversity (GoN 2014). A recent review reported more than 220 freshwater species in the country (Khatri et al 2020). However, because of its rich network of rivers and streams, the growing demand for electricity, drinking, and irrigation for increasing population, the damming and diversion of these ecosystems have become common (ADB 2018;WWAP 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sites specially located in urban and industrial areas in Nepal exhibited lower DO while high nutrient concentrations (Sah et al, 2000;Tachamo-Shah & Shah, 2012). Poor water quality has been documented as a major problem declining fish population in the country (Khatri et al, 2020).…”
Section: Water Quality Parameters Across the Three Clustersmentioning
confidence: 99%
“…Resident mammals such as the snow leopard (Panthera uncia), wild yak (Bos mutus), red panda (Ailurus fulgens) and musk deer (Moschus chrysogaster) are considered major flagship species of Nepal. In addition to a large number of reptiles and amphibians (Paudel et al, 2023), three endemic fish species have been recorded in the higher elevations of the province (Khatri et al, 2020). Protected areas within the two provinces include Shuklaphanata National Park, located in the lowland area, and in the mid-hills and higher mountainous area, protected areas include Khaptad National Park, Rara National Park, Shey Phoksundo National Park and Api-Nampa Conservation Area (DNPWC, 2023).…”
Section: Introductionmentioning
confidence: 99%